Knowledge, attitude, and perceptions towards the 2019 Coronavirus Pandemic: A bi-national survey in Africa - (:unkn) unknown (My University, 2020)
The current Coronavirus (COVID-19) pandemic has impacted and changed lives on a global scale since its emergence and spread from China in late 2019. It has caused millions of infections, and thousands of deaths worldwide. However, the control of this pandemic still remains unachievable in many African countries including Egypt and Nigeria, despite the application of some strict preventive and control measures. Therefore, this study assessed the knowledge, attitude, and perceptions of Egyptians and Nigerians towards the COVID-19 pandemic. This study was designed as a cross-sectional community-based questionnaire survey in both countries. Participants' demography, knowledge, attitude, and perceptions towards the COVID-19 outbreak were obtained using a convenience sampling technique. Data collected were subjected to descriptive statistics and logistic regression analysis. A total of 1437 respondents were included in this preliminary report. The mean knowledge score was 14.7±2.3. The majority of the respondents (61.6%) had a satisfactory knowledge of the disease. Age (18-39 years), education (College/bachelors), and background of respondents were factors influencing knowledge levels. The attitude of most respondents (68.9%) towards instituted preventive measures was satisfactory with an average attitude score of 6.9 ± 1.2. The majority of the respondents (96%) practiced self-isolation and socialdistancing but only 36% follow all health recommendations. The perception of most respondents (62.1%) on the global efforts at controlling the virus and preventing further spread was satisfactory with an average score of 10.9 ± 2.7. Only 22% of the respondents were satisfied with their country's handling of the pandemic. An apprehensive understanding of the current status in Africa through studies like KAP is crucial to avoid Africa being the next epicenter of the pandemic. For the populace to follow standard infection prevention and control
Keywords: African Research